Pengaruh Model Game Based Learning Terhadap Peningkatan Hasil Belajar Siswa Pada Materi Mitigasi Bencana Alam (Studi Kasus SMAN 1 Jakarta) - Rahmadita, Aulia Putri; Mataburu, Ilham Badaruddin; A’Rachman, Fauzi Ramadhoan (Peneliti.net, 2024)
This research aims to determine the effect of the Game Based Learning learning model on the learning outcomes of class XI IPS students on natural disaster mitigation material at SMA Negeri 1 Jakarta. The sampling technique in this research used the Simple Random Sampling method. The samples used in this research were class XI IPS 2 as the experimental class and class XI IPS 1 as the control class. In testing the data, the results obtained showed that there was an influence on the cognitive learning outcomes of students in the experimental class. The experimental class experienced an increase in cognitive learning outcomes, namely from 68 to 82. Meanwhile, the results for the control class were from 47.3 to 71. This conclusion is also supported by the acquisition of Sig. in the unpaired t test it is 0.005, which means that H0 is rejected and Ha is accepted because of the Sig value. < 0.05. So there is an increase in learning outcomes but it is not too influential after using the Game Based Learning model.